(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to reveal the degree of students’ commitment to the student ethics in the schools of the Northern Almazar District from the teachers’ perspective. The study population consisted of (950) male- and female-teachers from the school teachers the Northern Almazar District. In order to achieve the objectives of the study, the descriptive survey approach was used through developing a thirty-seven-item, and it was distributed to a sample consisting of (300) male- and female-teachers. The results of the study showed that the degree of commitment of students in the Northern Almazar District schools to the ethics of the student of knowledge from the teachers’ point of view was moderate. The results also indicated that there were statistically significant differences in the opinions of the study sample about the degree of students’ commitment to student ethics in the schools of the Northern Almazar District from the point of view of teachers which can be ascribed to gender, in favor of females, and to experience, in favor of the period of experience less than 10 years. As for the difference in specialization, the results indicated that there were no statistically significant differences. Accordingly, the study recommends the necessity of designing behavioral programs to confront the problems of students’ commitment to student ethics.